Adverse social experiences in adolescent rats result in enduring effects on social competence, pain sensitivity and endocannabinoid signaling - Schneider, Peggy; Schmahl, Christian; Bohus, Martin; Meyer-Lindenberg, Andreas; Spanagel, Rainer; Schneider, Miriam (Frontiers in behavioral neuroscience, 2016)
Social affiliation is essential for many species and gains significant importance during adolescence. Disturbances in social affiliation, in particular social rejection experiences during adolescence, affect an individual’s well-being and are involved in the emergence of psychiatric disorders. The underlying mechanisms are still unknown, partly because of a lack of valid animal models. By using a novel animal model for social peer-rejection, which compromises adolescent rats in their ability to appropriately engage in playful activities, here we report on persistent impairments in social behavior and dysregulations in the endocannabinoid system. From postnatal day (pd) 21 to pd 50 adolescent female Wistar rats were either reared with same-strain partners (control) or within a group of Fischer 344 rats (inadequate social rearing, ISR), previously shown to serve as inadequate play partners for the Wistar strain. Adult ISR animals showed pronounced deficits in social interaction, social memory, processing of socially transmitted information, and decreased pain sensitivity. Molecular analysis revealed increased CB1 receptor protein levels and CP55,940 stimulated [35S]GTPγS binding activity specifically in the amygdala and thalamus in previously peer-rejected rats. Along with these changes, increased levels of the endocannabinoid anandamide and a corresponding decrease of its degrading enzyme fatty acid amide hydrolase were seen in the amygdala. Our data indicate lasting consequences in social behavior and pain sensitivity following peer-rejection in adolescent female rats. These behavioral impairments are accompanied by persistent alterations in CB1 receptor signaling. Finally, we provide a novel translational approach to characterize neurobiological processes underlying social peer-rejection in adolescence.